A case of a common bile duct stone that formed around a fish bone as a nidus after distal gastrectomy with Roux-en-Y reconstruction - Ken Hirata; Daichi Kawamura; Masahiko Orita (Surgical Case Reports, 2021)
Abstract Background The presence of a foreign body in the common bile duct (CBD) is a rare phenomenon. Thus, the route and mechanism of its migration remain difficult to fully clarify, especially for cases that occur after gastrectomy with Roux-en-Y reconstruction. Herein, we present a case of a CBD stone that formed around a fish bone as a nidus subsequent to distal gastrectomy with Roux-en-Y reconstruction. Case presentation A 70-year-old man was admitted to our hospital due to repeated episodes of epigastralgia. He had undergone distal gastrectomy with Roux-en-Y reconstruction for gastric cancer approximately 10 years prior. Blood tests revealed obstructive jaundice, hepatobiliary dysfunction, and inflammation. Multi-plane reconstructed computed tomography (CT) revealed a CBD stone with a needle-shaped calcification density at the center, oriented along the length of the CBD. Surgery was performed using an upper median laparotomy approach. Lithotomy with choledochotomy was performed to remove one fragile bilirubin stone that had formed around a 3-cm, needle-shaped fish bone. A choledochoduodenal fistula was not detected intraoperatively. A review of the imaging of a prior examination revealed that the formation of the CBD stone around the fish bone was observable on a follow-up CT performed approximately 2 years prior. However, no clinical symptoms associated with the migration of the fish bone to the CBD were reported and the fish bone was not detected at that time. Conclusion In this case, transpapillary migration of the fish bone could only be speculated in the absence of an observable fistula, choledochostomy, or any clinical symptoms. Our case is clinically relevant as cholangitis developed after CBD stone formation around the fish bone that acted as a nidus.